“One-Pot” Synthesis of 4-Substituted 1,5-Diaryl-1H-pyrazole-3-carboxylic Acids via a MeONa/LiCl-Mediated Sterically Hindered Claisen Condensation–Knorr Reaction–Hydrolysis Sequence - Jiang, Jian-An; Du, Cai-Yan; Gu, Chun-Hui; Ji, Ya-Fei (Synlett, 2012)
A “one-pot” synthesis of 4-substituted 1,5-diaryl-1H-pyrazole-3-carboxylic acids was first reported in moderate to good yields. This concise procedure, featuring efficiency and green chemistry, was composed of MeONa/LiCl-mediated sterically hindered Claisen condensation, Knorr reaction and hydrolysis.
Keywords: MeONa/LiCl; sterically hindered Claisen condensation; Knorr reaction; 4-substituted 1,5-diaryl-1H-pyrazole-3-carboxylic acids; “one-pot” synthesis